Factores de riesgo para la transmisión de leishmaniasis cutánea en niños de 0 a 5 años en un área endémica de Leishmania (Viannia) braziliensis - Ampuero Vela, Julia Sonia (2005)
With the purpose of identifying risk factors for cutaneous leishmaniasis transmission in children from 0 to 5 years, a matched case-control study was carried out in Corte de Pedra, Bahia, Brazil, an endemic area of Leishmania (Viannia) braziliensis. Children with a positive leishmanin skin test and one or more active lesions or scars consistent with cutaneous leishmaniasis were defined as cases. Forty cases and 71 controls were selected and matched by age and place of residence. The presence of a family member with a history of cutaneous leishmaniasis in the year prior to the appearance of the disease in the child was found to be an important risk factor (MÔRMH = 17.75; 95%CI: 4.08-77.25). No evidence of association between the disease and other risk factors was found, such as child’s habits inside or outside the house, domiciliary or peridomiciliary characteristics, or presence of vectors or probable reservoir animals. These findings support the hypothesis that humans serve as both the reservoir and source of infection for this age group.